Satellite or ground-based measurements for production of site specific hourly irradiance data: Which is most accurate and where?. (1st May 2018) - Palmer, Diane; Koubli, Elena; Cole, Ian; Betts, Tom; Gottschalg, Ralph
Graphical abstract: Highlights: Provides a national assessment of solar irradiance models. Weather station density is fundamental for irradiance model selection. Choice of satellite model and temporal resolution of inputs is also influential. Irradiance model additionally determined by terrain ruggedness and latitude. Accuracy of all models is influenced by a combination of factors. Abstract: Site-specific satellite-derived hourly global horizontal irradiance is compared with that obtained from extrapolation and interpolation of values measured by ground-based weather stations. A national assessment of three satellite models and two ground-based techniques is described. A number of physiographic factors are examined to allow identification of the optimal resource. The chief influences are determined as: factors associated with latitude; terrain ruggedness; and weather station clustering/density. Whilst these factors act in combination, weather station density was found to be fundamental for a country like the UK, with its ever-changing weather. The decision between satellite and ground-based irradiance data based on accuracy is not straightforward. It depends on the exactitude of the selected satellite model and the concentration of pyranometric stations.